2009
DOI: 10.4047/jap.2009.1.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adhesive primers on bonding strength of heat cure denture base resin to cast titanium and cobalt-chromium alloy

Abstract: STATEMENT OF PROBLEMThe poor chemical bonding of a denture base resin to cast titanium framework often introduces adhesive failure and increases microleakage.PURPOSEThis study evaluated the shear bond strengths of a heat cure denture base resin to commercially pure titanium, Ti-6Al-4V alloy and a cobalt-chromium alloy using two adhesive primers.MATERIAL AND METHODSDisks of commercially pure titanium, Ti-6Al-4V alloy and a cobalt-chromium alloy were cast. Specimens without the primer were also prepared and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Several studies have revealed that thermal stress induced by thermocycling weakens the adhesive bonding between resin-based materials and cast CoCr alloys, but priming with 10-methacryloxydecyl dihydrogen phosphate (MDP) significantly improved the bonding durability [12][13][14][15][16][17][18][19] . However, no information is available regarding adhesive bonding between resin composites and laser-sintered Co-Cr alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that thermal stress induced by thermocycling weakens the adhesive bonding between resin-based materials and cast CoCr alloys, but priming with 10-methacryloxydecyl dihydrogen phosphate (MDP) significantly improved the bonding durability [12][13][14][15][16][17][18][19] . However, no information is available regarding adhesive bonding between resin composites and laser-sintered Co-Cr alloys.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 6-MHPA promotes adhesive bonding to base metals, but 10-MDDT has an affinity for noble metals rather than base metals [28]. The use of primers containing MDP improved the retention strength between some resin-based materials and cast CoCr alloy [17][18][19][20][21][22][23], and the effect of MDP as an adhesivepromoting monomer for cast Co-Cr alloy was higher than that of 6-MHPA [24,29]. The present results also suggest that MDP is superior to 6-MHPA as an adhesive-promoting monomer for a laser-sintered Co-Cr alloy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that priming with 10-methacryloyloxydecyl dihydrogen phosphate (MDP) significantly improved the retention strength between some resin-based materials and cast Co-Cr alloy [17][18][19][20][21][22][23][24][25]. The authors previously reported that laser-sintered Co-Cr alloy specimens with retention devices provided better retention and higher retention strength than cast Co-Cr alloy specimens with retention beads [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been developed to improve bond strength between dental alloys and PMMA; these approaches are usually based on modifying the topography (mechanical) and/or chemical composition of the alloy surface to increase the alloy‐polymer interaction . Topographic irregularities and surface roughness can be achieved by acid etching, air‐abrasion or by adding topographic features including beads, posts, meshes, and bars .…”
Section: The Bond Strengths Between Dental Alloys (Ti and Cocr) And Pmentioning
confidence: 99%